Analysis Of Family Support And Quality of Health Cervice FHE The Utilization of VCT Poly and Compliance of HIV/AIDS Patients in Under Going Antiretroviral Therapy (ARV) in RSUD Gambiran Kediri City - Hayati, Anis Khoirin; Siyoto, Sandu; Wardhani, Ratna (Universitas STRADA Indonesia, 2024)
HIV / AIDS is a frightening disease for the people of Indonesia today, so people with HIV / AIDS often get excessive stigma and discrimination. The design of this study was an observational quantitative study with a cross section approach with the focus of the research directed to be to analyze family support and service quality for the utilization of VCT Poly and HIV / AIDS patient compliance in undergoing antiretroviral therapy (ARV) in Gambiran City Hospital in Kediri with a sample of 109 respondents taken by the Accidental Sampling technique. The result were found that the majority of respondents had sufficient family support as many as 56 respondents (51.4%). Most respondents rated that the quality of service in the category of 56 respondents was sufficient (51.4%). Most respondents had medium category utilization of 55 respondents (50.5%). Most respondents were not compliant to undergo antiretroviral therapy (ARV) as many as 65 respondents (59.6%). The results of the study using the Path Analysis Test showed that the p-value <0.05 then H0 was rejected and H1 was accepted so it was concluded that there was a significant influence of family support and service quality through the use of VCT Poly to the compliance of HIV / AIDS patients in undergoing antiretroviral therapy ( ARV) at Gambiran City Hospital in Kediri. The compliance of HIV / AIDS patients in undergoing antiretroviral (ARV) therapy is influenced by family support, quality of service and utilization in the VCT Poly itself. So that patients need to be given good support as well as improving the quality of services available in the VCT Poly.